Chloride absorption in salt-sensitive Carrizo citrange and salt-tolerant Cleopatra mandarin citrus rootstocks is linked to water use - Moya, José L.; Gómez-Cadenas, Aurelio; Primo-Millo, Eduardo; Talón, Manuel (2017)
In this work, seedlings of two citrus rootstocks, the salt‐tolerant Cleopatra mandarin (Citrus reshni Hort. ex Tan.) and the salt‐sensitive Carrizo citrange (Citrus sinensis [L.] Osb. × Poncirus trifoliata [L.] Raf.) were used to study the relationship between chloride and water uptake. The results indicated that net chloride uptake rates in both genotypes were alike and decreased linearly with the time of salinity exposure, although they were more rapidly reduced in the tolerant genotype. In each rootstock, chloride uptake rates paralleled the decreases in transpiration rates. When transpiration was modified, concomitant changes in leaf Cl– concentrations were observed. There was a high positive correlation between total chloride content per plant and total water absorbed. In addition, the data indicate that the tolerant genotype ‘excluded’ more chloride, i.e. it absorbed lower amounts of chloride per volume of water. Cleopatra also possessed a less efficient root system for water uptake and a higher shoot‐to‐root ratio. The results show that, overall, chloride absorption is linked to water use and that further tolerance in Cleopatra is mostly conferred by superior root resistance to Cl– uptake. Therefore, it is proposed that chloride absorption and, hence, salt tolerance in citrus depends to a great extent upon water use.